2022
DOI: 10.1016/j.heliyon.2022.e08732
|View full text |Cite
|
Sign up to set email alerts
|

Bio methane potential of sludge from municipal sewer and exchange stations

Abstract: Technologies with resource recovery alternatives are suggested in metropolitan settings. Anaerobic digesters (AD) are the most common. The use of microcrystalline cellulose and a variety of grocery products as control feed increases the cost of bio methane potential analysis (BMP). This limits its replication, especially in developing countries. As a result, this study looks into the use of milled paper as a control feed during BMP analysis of sludge from sewer and exchange stations. A batch experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Similarly, Hung et al (2015) reported the average pH of the sludge samples collected from Ha Noi, Vietnam, was in the range of neutral to alkaline (7.04-7.4). In contrast to this, Selamawit and Agizew (2022) reported that the pH values of the sludge samples obtained from wastewater collected from the sewerage system and exchange stations were 5.1 and 6.9, respectively. Sudiartha et al (2022) reported that the pH of the aerated sludge sample was 7.09, and this value increases as the temperature increases.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Similarly, Hung et al (2015) reported the average pH of the sludge samples collected from Ha Noi, Vietnam, was in the range of neutral to alkaline (7.04-7.4). In contrast to this, Selamawit and Agizew (2022) reported that the pH values of the sludge samples obtained from wastewater collected from the sewerage system and exchange stations were 5.1 and 6.9, respectively. Sudiartha et al (2022) reported that the pH of the aerated sludge sample was 7.09, and this value increases as the temperature increases.…”
Section: Resultsmentioning
confidence: 74%
“…Sewage sludge can be treated using biochemical, thermochemical, or mechanical methods to generate biogas. Recently, researchers have suggested that sludge has a lot of potential for gas production (Selamawit and Agizew 2022). According to a review report, the sludge of shrimp ponds contains particulate and dissolved organics such as microorganisms, leftover shrimp food, shrimp manure, and other organic substances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study by Al-samet et al showed that mixing sewage sludge with food waste had a synergistic effect that increased the amount of methane produced and enhanced the efficiency of the anaerobic digestion process [46]. Moreover, Selamwit and Agizew conducted the biomethane potential analysis (BMP) on a lab scale, and the results showed that the energy recovered from SS has an electric potential of 8.81 kWh [47]. Additionally, under the premise of sustainability, SS can be seen as a renewable energy source, and its combustion produces significantly fewer greenhouse gas emissions than fossil fuel energy output.…”
Section: Sewage Sludge (Ss)mentioning
confidence: 99%
“…Nowadays, the sludge is landfilled [40], gasified, or pyrolyzed [41]. Every year, up to 10 million tonnes of dry sewage sludge are produced worldwide [42], and the number is still increasing due to the growing urban population and urbanization [43]. Legislation related to sewage sludge management has been very strict to ensure safe sludge usage in industry, especially in the EU, since the implementation of the new Urban Waste Water Treatment Directive (91/271/CEE) [44], which has also brought an increase in the installation of the wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%